2018 21st International Conference on Intelligent Transportation Systems (ITSC) 2018
DOI: 10.1109/itsc.2018.8569227
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pricing in One-Sided Autonomous Ride-Sourcing Markets

Abstract: Dynamic pricing has been used by Transportation Network Companies (TNCs) to achieve a balance between the volume of ride requests with numbers of available drivers on two-sided TNC markets. Given the desire to reduce operating costs and the emergence of Autonomous Vehicles (AVs), the introduction of TNC-owned AV fleets could convert such services into one-sided markets, where operators have full control of service supply. In this paper we investigate the impact of utility-based dynamic pricing for Autonomous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The current fare levels of ridesourcing services may present considerable barriers to frequent service adoption for many people. Considering that future AV technologies may reduce the cost of ridesourcing services by removing the cost associated with human drivers (Compostella et al 2020;Walker Johnson, 2016;Stocker and Shaheen 2018;Spieser et al 2014;Karamanis et al 2018), this study employed SP scenarios where the ridesourcing costs were decreased to be more comparable with driving costs. With this experiment, we were able to focus on other potential barriers (such as attitudes, habits, and perceptions, etc.)…”
Section: Attitudinal Factorsmentioning
confidence: 99%
“…The current fare levels of ridesourcing services may present considerable barriers to frequent service adoption for many people. Considering that future AV technologies may reduce the cost of ridesourcing services by removing the cost associated with human drivers (Compostella et al 2020;Walker Johnson, 2016;Stocker and Shaheen 2018;Spieser et al 2014;Karamanis et al 2018), this study employed SP scenarios where the ridesourcing costs were decreased to be more comparable with driving costs. With this experiment, we were able to focus on other potential barriers (such as attitudes, habits, and perceptions, etc.)…”
Section: Attitudinal Factorsmentioning
confidence: 99%
“…Considering our resource allocation problem introduced in Section II-A, we can regard the vertices v ∈ A as source vertices since these constitute the initial states of all vehicles in the fleet. In a similar fashion, the vertices in C can be identified as sinks, however; their balance vectors cannot be defined in advance, as certain demand requirements might lead to violation of (5).…”
Section: B Non-linear Minimum Cost Flow Formulationmentioning
confidence: 99%
“…matching platforms to fleet operators having complete control of the supply [4]. In such a scenario, currently implemented dynamic pricing strategies would still suppress demand [5], but TNCs, as fleet owners, would need to decide vehicle redistribution operations. Generally, in the absence of drivers entering the market proactively by knowing historical surge pricing patterns [2], autonomous vehicle ride-sourcing operators would need to manage their fleet effectively, to alleviate any asymmetries of demand across road-networks.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that all vehicles will be assigned, the set of all path-vehicle allocations is Proof. We reduce an instance of MWIS, a known APX-hard 6 problem [19], to an instance of Model 2. Given a weighted graph G = (V, E, w), the MWIS objective is to find a set of pairwise disjoint nodes S ⊆ V with maximum total weight.…”
Section: Reduction To Maximum Weighted Independent Setmentioning
confidence: 99%
“…Vehicles (AVs) in the near future, their platforms are likely to be transformed into one-sided markets, where they will enjoy complete control of the supply [5]. Previous work by Karamanis et al [6] demonstrated that such platforms can still incentivise the use of shared rides or PT transport while remaining profitable.…”
Section: Introductionmentioning
confidence: 99%